„Ale to chyba nie jest wilamowskie”. Mniej znane wyznaczniki odrębności kulturowej Wilamowian - Tymoteusz Król (Adeptus, 2022)
“But this doesn’t look Vilamovian”: Lesser-Known Determinants of the Cultural Distinctiveness of Vilamovians Researchers who study Wilamowice regard the costume and language as the main determinants of the cultural distinctiveness of the Vilamovians. The representatives of this ethnic group themselves also presented them as the most important. This was probably the case before 1945, when the folk dress and language began to disappear due to the post-war persecutions. Today, they still remain important markers of Vilamovianness, but are rarely used in everyday life. The article presents the determinants of Vilamovian distinctiveness that are important for contemporary Vilamovians, especially for young people involved in linguistic revitalisation. These are, among others, Vilamovian Polish, multilingualism, Vilamovian Christmas songs, Vilamovian-style scrambled eggs, Vilamovian Christmas Eve noodles and drinking from one glass. Although they are also found in other regions, including nearby villages, they are an equally important attribute of Vilamovianness for many Vilamovians. More important than their “objective” uniqueness is the fact that during the research carried out by the author, particularly young people from Wilamowice considered them appropriate for expressing their identity and the cultural distinctiveness related to it. Perhaps in the future some of them will become more important for Vilamovians than the costume or language. Ethnic boundaries are not the result of members of an ethnic community having a separate culture, but of their actions in order to distinguish themselves from others. „Ale to chyba nie jest wilamowskie”. Mniej znane wyznaczniki odrębności kulturowej Wilamowian Badacze zajmujący się Wilamowicami za główne wyznaczniki odrębności kulturowej Wilamowian uznają strój i język. Również sami przedstawiciele tej grupy etnicznej prezentowali je jako najważniejsze. Tak było zapewne przed 1945 rokiem, lecz w wyniku powojennych prześladowań zaczęły one zanikać. Dziś nadal stanowią ważne ...